Changes in microbial and metabolic profiles of mice fed with long-term high salt diet - Huiying Tian; Xiaotang Gao; Hanlin Du; Zhuofeng Lin; Xianen Huang (BMC Gastroenterology)
Abstract Purpose High salt diet (HSD) has been considered as a risk factor for the development of metabolic disorders. However, less is known about long-term implications of HSD. Therefore, the aim of this study was to conduct a preliminary investigation into the effects of mice feeding with long-term HSD on gut microbial and metabolic profiles. Methods In this study, C57BL/6 J mice were fed with HSD for 22 weeks, after which fat and feces were collected. The composition of fecal microbiota was determined using 16S rRNA gene sequencing. Fecal metabolic profiling of mice was identified through untargeted ultrahigh-performance liquid chromatography-mass spectrometry. In addition, the serum levels of adipocytokines, including fibroblast growth factor 21 (FGF21) and adiponectin (APN), were measured. Results Long-term HSD disrupted the growth performance of mice. Compared to those fed a normal salt diet, mice on a long-term HSD showed slower weight gain, as well as lower fat accumulation and serum levels of APN, while experiencing elevated blood pressure and levels of serum FGF21 and glucose. The 16S rRNA sequencing revealed changes in community richness and diversity, with long-term HSD affecting the abundance of certain gut microbiota, including Firmicutes, Christensenella, Barnesiella, and Lactococcus. Fecal metabolomic analysis also uncovered alterations in metabolites, such as myriocin, cerulenin, norcholic acid, 7-ketocholesterol, and prostaglandins B2. Further analysis indicated that these gut and microbiota and metabolites are predominantly involved in the lipid metabolism of the organism. Importantly, variations in these gut metabolites and microbiota were significantly correlated with body weight, fat accumulation, and the levels of FGF21 and APN. Conclusion Long-term HSD affects physiological traits, alters gut metabolites profiles, and impacts the composition and function of gut microbiota, thus causes a certain impact on lipid metabolism.